Sugar-Sweetened Beverage Consumption, Contributing Factor, and Weight Outcomes in Adolescents: A Scoping Review - Erma Wahyu Mashfufa; Nur Aini; Ollyvia Freeska Dwi Martha; Imam Fahril (Journal of Ners and Midwifery, 2026)
High consumption of sugar-sweetened beverages (SSBs) is strongly associated with adolescent obesity and related conditions, including type 2 diabetes and cardiovascular disease. This pattern is driven by easy access, low cost, and aggressive marketing, especially in developing countries. Understanding the determinants of SSB intake and its effects on weight is essential for guiding public health strategies. This study aims to explore evidence on SSB consumption, its contributing factors, and its relationship with weight-related outcomes among adolescents. A scoping review was conducted using PubMed, Scopus, Embase, MEDLINE (Ovid), and Web of Science, with additional manual searches via Google Scholar. Keywords included “Adolescents,” “Sugar-Sweetened Beverages,” and “Obesity.” Studies were included if they involved adolescents consuming SSBs. A total of 34 studies with 218,767 adolescent participants were analyzed. SSB consumption varied and was influenced by factors such as availability at home and school, peer influence, and health knowledge. High intake was consistently linked to increased obesity risk, with frequent consumers showing higher BMI. Reducing SSB access at home and school, along with improving awareness, emerged as important strategies to limit adverse health impacts. Elevated SSB consumption among adolescents is closely linked to overweight and obesity. Targeted interventions, including early screening, educational initiatives for adolescents and parents, and policies restricting availability in schools and communities, are needed to reduce intake and associated health risks.